Factors Affected to Poor Attendance of Advance Level Students - Wickramanayake, Roshani; Kumari, H. M. Lalitha (Researchparks Publishing, 2023)
The purpose of this research was to study the factors that affect for poor attendance of Advance Level students in 1AB schools. The study was focused to get an insight idea on school related factors for students’ poor attendance and family related factors that caused for school absenteeism. Concurrent mix methodology was followed and the data was collected by survey questionnaires and by interviews. The questionnaires were given both students and parents who selected randomly for the samples. The survey samples were consisted of 92 Advance Level students and 46 of their parents. 8 Advance Level class teachers were selected purposively for interviews. Survey data was analyzed by descriptive statistical methods using tables, graphs and percentages and interview data was analyzed by thematic analysis. The study divulged the major school related factors that caused for school absenteeism as; unsuitable teaching methods, lack of school facilities and lack of enthusiasm for schooling. Other than that heavy work load, writing lesson notes, and non-conduct of practical tests were also caused in minor level. And also, parents’ income, lack of parents’ attention, helping to parents, failure to accept parental advices and educational level of parents were found out as major family related factors that caused for absenteeism. Look after younger siblings and broken families were also found out as the factors that caused for absenteeism in minor level.